Environmental Communication through Corporate Social Responsibility in Overcoming Peatland Fire Problems - Yasir (International Journal of Social Science and Business, 2023)
Corporate communications should be integrated with environmental conservation campaigns. This research aims to explore the role of Pertamina's CSR in overcoming environmental problems related to peatland fires in Bukit Batu District, Bengkalis Regency. The researcher used a qualitative method with a case study approach. The subjects of this research are Pertamina's CSR practitioners and the community. The results show that Pertamina's CSR contributes in campaigning for environmental sustainability and preventing forest fires through the program of "Kampung Gambut Berdikari". CSR communication is carried out on a group basis, namely the Tunas Makmur Farmers Group and the Fire Care Community (MPA) forum to tackle and prevent fires on peatlands. These CSR activities increases environmental awareness and improves the economic welfare of the community. The activities are based on the development of peat arboretum ecotourism and the development of pineapple plantations. This peat arboretum ecotourism becomes an important communication medium to educate the farming community, school students, youth and also visitors. CSR activities should not only be oriented towards corporate image, but its success can be imitated, transmitted and developed in other areas prone to fire disasters.